High Gain Superstrate Loaded Membrane Antenna Based on Substrate Integrated Waveguide Technology - Hamsakutty Vettikalladi (International Journal of Antennas and Propagation)
The design and the results of a single slot coupled substrate integrated waveguide (SIW) fed membrane antenna loaded with a superstrate layer are presented for 94 GHz communication system. The membrane antenna is designed using ANSYS HFSS and consists of 6 layers. The microstrip patch antenna (MPA) placed on the top pyralux substrate layer is excited by means of a longitudinal rectangular slot placed over the SIW structure in the bottom pyralux substrate. The simulated antenna impedance bandwidth is found to be 5 GHz (91.5–96.5 GHz) with a gain of 7 dBi. In order to improve the gain a superstrate layer is added above the membrane antenna. The maximum gain achieved is 14.4 dBi with an efficiency of 77.6% at 94 GHz. The results are verified using CST Microwave Studio and are found to be in good agreement.